The Performance of IPO Equity Valuation Techniques: Recent Evidences from China Stock Market - Feng, Qi (2011)
This paper uses financial forecasts and valuation information provided by lead underwriters to examine the valuation accuracy of Discounted Cash Flow (DCF) and Comparable Firm Multiples Methods on 50 IPOs in China market. The results show that P/E and P/B methods provide more accurate estimation of actual market price than DCF model. No evidences were found to show that P/E method implemented by lead underwriters result in better valuations than that being implemented mechanically(typically by academics). P/E method using trailing earnings are found to be weakest in all cases, while using forecast earnings yields more precise valuation. As a research feature, this paper also suggests that underwriters do not alter their valuation model choice across listing markets and firm’s characteristics. However, DCF is proved to be more accurate when pricing relatively large and mature firms; while P/E method is better in pricing issues in growth enterprise market. Finally, no evidences found to support any value-added by the investment bankers during the IPO pricing as the final offer price is not found to be a better predictor of market price than value estimated by valuation models.